The HELLAS2XMM survey: XI. Unveiling the nature of X-ray bright optically normal galaxies - Civano, F.; Mignoli, M.; Comastri, A.; Vignali, C.; Fiore, F.; Pozzetti, L.; Brusa, M.; La Franca, F.; Matt, G.; Puccetti, S.; Cocchia, F. (Astronomy and astrophysics (Berlin), 2007)
Aims. X-ray bright optically normal galaxies (XBONGs) constitute a small but significant fraction of hard X-ray selected sources in recent Chandra and XMM- Newton surveys. Even though several possibilities were proposed to explain why a relatively luminous hard X-ray source does not leave any significant signature of its presence in terms of optical emission lines, the nature of XBONGs is still subject of debate. We aim to better understand their nature by means of a multiwavelength and morphological analysis of a small sample of these sources. Methods. Good-quality photometric near-infrared data (ISAAC/VLT) of four low-redshift (z = 0.1- 0.3) XBONGs, selected from the HELLAS2XMM survey, have been used to search for the presence of the putative nucleus, applying the surface-brightness decomposition technique through the least-squares fitting program GALFIT. Results. The surface brightness decomposition allows us to reveal a nuclear point-like source, likely to be responsible for the X-ray emission, in two out of the four sources. The results indicate that moderate amounts of gas and dust, covering a large solid angle (possibly 4π) at the nuclear source, combined with the low nuclear activity, may explain the lack of optical emission lines. The third XBONG is associated with an X-ray extended source and no nuclear excess is detected in the near infrared at the limits of our observations. The last source is associated to a close (d≤ 1 arcsec) double system and the fitting procedure cannot achieve a firm conclusion.